Rare earth lubricated high-speed train brake pad and preparation method thereof
By regulating the iron-copper ratio, designing components in the brake pads, and introducing rare earth elements, the problem of excessive friction interface temperature at high speeds of existing copper-based brake pads is solved, and a high-performance brake pad material that can match the carbon ceramic disk well at speeds of 400km/h or above was prepared.
Patent Information
- Application Number
- CN202411811977.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
When existing copper-based brake pads are grinding with carbon ceramic discs in high-speed trains above 400km/h, the friction interface temperature is too high, resulting in insufficient high temperature strength of the material, making it difficult to meet the demand for higher braking speeds.
Through iron-copper ratio regulation, reasonable design of other components and the introduction of rare earth elements, a rare earth-lubricated high-speed train brake pad was prepared. The material includes mixed powders of iron and copper, graphite powder, alumina fibers, high-carbon iron chromium powder, chromium powder and rare earth elements, and is prepared by cold press forming and hot press sintering processes.
The material exhibits excellent friction and wear performance at braking speeds of 400km/h and above, has high strength and wide temperature lubrication capabilities, and can match well with the carbon ceramic brake disc, reduce the temperature of the friction interface, and extend the material life.
Smart Images

Figure CN119588929A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of producing high-speed train brake pads by powder metallurgy process, and in particular provides a rare earth lubricated high-speed train brake pad suitable for braking matched with a carbon ceramic disc and a preparation method thereof. Background Art
[0002] The copper-based brake pads prepared by powder metallurgy show excellent friction and wear performance, good thermal conductivity and environmental adaptability when grinding against steel discs. They are one of the core key components in the braking system of 200-350km / h high-speed EMUs. However, with the proposal of the "CR450 Science and Technology Innovation Project Implementation Plan" of the National Railway Group in 2021, the operating speed of the new generation of "Fuxing" EMU CR450 under development will reach 400km / h. Taking the existing CRH380B EMU as an example, the braking energy required for emergency braking at 400km / h increases by 30% compared with 350km / h, which also brings huge challenges to the braking system, mainly reflected in the high temperature between the friction interfaces caused by high kinetic energy conversion. Carbon ceramic (C / C-SiC) brake discs with low density, high strength, excellent fatigue resistance and stable high-temperature friction and wear performance have become one of the important means to replace traditional alloy steel brake discs for higher braking speed conditions and lightweight train braking systems. However, compared with alloy steel discs, the temperature rise effect of the friction interface is more significant when carbon ceramic brake discs are involved in braking. When the existing copper-based brake pads are rubbed against carbon ceramic discs at 400km / h, the average temperature of the friction interface is maintained above 700℃ for a long time, and the instantaneous temperature can reach 1000℃, which is close to the melting point of pure copper (1083℃). This shows that the insufficient high-temperature strength of the copper matrix restricts its further application in high-speed trains ≥350km / h, and it is urgent to develop brake pads with better high-temperature mechanical properties and friction and wear properties.
[0003] At present, common brake pad materials include resin-based brake pads and iron-based brake pads. Resin-based brake pad materials are not suitable for use under high-speed and heavy-load conditions because they use organic resin as the matrix. This is mainly affected by the insufficient high-temperature strength of the matrix. For example, the thermal decomposition temperature of commercial phenolic resin does not exceed 400°C. Iron-based brake pads are cheap and have higher high-temperature strength. They are widely used in aircraft, tanks and other heavy-load special vehicles. Patent CN104399970B "An iron-based powder metallurgy friction material and its preparation method" prepares iron-based friction materials for use at low speeds by adding iron powder, copper powder, manganese powder, graphite powder, silicon carbide powder, molybdenum disulfide powder, silicon dioxide powder, aluminum oxide powder and precipitated barium sulfate powder. Patent CN106086718B "A clutch iron-based composite friction material and its preparation method" uses gray cast iron powder or ductile iron powder, wear-resistant powder, graphite powder and carbon fiber to prepare iron-based friction materials for clutches. Patent CN112059171B has developed a powder metallurgy brake pad that matches a carbon ceramic disc, which mainly contains iron powder, copper powder, flake graphite, graphene, ferrous sulfide powder, spherical chromium powder, molybdenum powder, chromium iron alloy powder, molybdenum iron alloy powder, silicon carbide and titanium dioxide. Due to the need to use spray bonding and shock pressure sintering, its preparation process is complicated, the product cycle is long, and the cost is also increased. Based on the above, it can be seen that there is currently no invention specifically for brake pad materials matching carbon ceramic discs for 400km / h and above. Summary of the invention
[0004] In view of the above situation, the present invention proposes a rare earth lubricated high-speed train brake pad and a preparation method. By adjusting the iron-copper ratio, rationally designing other components and introducing rare earth elements, a brake pad material that can match the carbon-ceramic brake disc and has excellent friction and wear performance at a braking speed of ≥400km / h is prepared. The preparation process is simple and the material is suitable for large-scale production.
[0005] A rare earth lubricated high-speed train brake pad and a preparation method thereof, comprising the following components:
[0006] Mixed powder of iron and copper: 50-80 parts by weight; mixed powder of flake graphite and granular graphite, 5-20 parts by weight; molybdenum disulfide powder: 0.5-5 parts by weight; alumina fiber: 0.5-5 parts by weight; high carbon ferrochrome powder: 1-10 parts by weight; chromium powder: 1-10 parts by weight; rare earth elements: 0.1-1.5 parts by weight.
[0007] Furthermore, the rare earth element is lanthanum or cerium, which is added in the form of iron-lanthanum, iron-cerium, copper-lanthanum or copper-cerium master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 15%-30%.
[0008] Furthermore, the average diameter of the alumina fiber is 0.1-10 μm, and the aspect ratio is 50-100.
[0009] Furthermore, in the mixed powder of flake graphite and granular graphite, the particle size of the flake graphite is 250-600 μm, the particle size of the granular graphite is 150-250 μm, and the ratio of the flake graphite to the granular graphite is 1:2-2:1.
[0010] Furthermore, the mixed powder of iron and copper, the iron powder is atomized iron powder, copper-clad iron powder or a mixture of the two in any proportion, with a particle size of 38-80 μm, and the copper powder is electrolytic copper powder, with a particle size of 38-80 μm.
[0011] Furthermore, the mixed powder of iron and copper, after including the amount of the master alloy introduced, has a ratio of iron to copper of 1:1-5:1.
[0012] Another object of the present invention is to provide a method for preparing a rare earth lubricated high-speed train brake pad, comprising the following steps:
[0013] (1) After weighing the above-designed components according to weight, weigh kerosene accounting for 1% of the weight of the powder, and transfer them into a double-conical mixing barrel for mixing;
[0014] (2) cold pressing the uniformly mixed powder into a shape;
[0015] (3) sintering the cold green body in a hot pressing sintering furnace;
[0016] (4) Cool to below 100°C and take out, keeping the pressure unchanged during the cooling process.
[0017] Furthermore, the rotation speed of the mixing drum in S1) is 50-100 rpm, and the mixing time is 4-6h.
[0018] Furthermore, the pressure in S2) is 300-600 MPa, and the holding time is 60-90 s.
[0019] Furthermore, the sintering process in S3) includes two steps of continuous low-temperature and high-temperature sintering. The low-temperature sintering temperature is 700-800°C, and the heat preservation time is 30-60 minutes. The high-temperature sintering temperature is 1000-1200°C, and the heat preservation time is 30-90 minutes. The atmosphere is a hydrogen-nitrogen mixed gas. During the entire sintering process, the pressure is 2-5MPa.
[0020] Principle explanation and beneficial effects:
[0021] The core requirement of the brake pad material matched with the carbon ceramic disc is that the friction interface can remain stable at a temperature of up to 1000°C, which requires the friction surface to have both excellent strength and high-temperature lubricity. To solve this problem, the present invention first improves the high-temperature strength of the brake pad material by increasing the iron content in the matrix. However, iron is easily oxidized at high temperatures to form a high-hardness and brittle friction oxide film, which fatigues and cracks under continuous stress, and the broken hard particles will cause abnormal damage to the friction surface. Therefore, it is necessary to retain a certain proportion of copper, which can play a role similar to a binder on the friction surface and promote the formation of the friction film. Flake graphite can play a lubricating role below 400°C, and the addition of molybdenum disulfide can further broaden the temperature of the lubrication effect to 650°C; in order to further improve the matching effect of the brake pad material with the carbon ceramic disc at various braking speeds and the high-temperature lubrication performance, rare earth elements cerium or lanthanum are introduced. In addition to purifying the organization and promoting sintering densification, rare earth elements are oxidized to form rare earth oxides when exposed to the friction surface during the friction process. At low temperatures, rare earth oxides exhibit the properties of particles, which can strengthen the friction film. At high temperatures, they promote the formation of a smooth and dense oxide film on the friction surface to produce high-temperature lubrication performance, and help prevent further contact and reaction between the metal and the surrounding environment, minimizing wear, thereby improving the friction braking performance of the brake pad material at high temperatures. In addition, chromium diffuses with iron during sintering, resulting in the porous nature of chromium particles. Under mild braking conditions, porous chromium has a low degree of fragmentation and acts as a large particle, while rare earth oxides play a major reinforcing role in the friction film; under extreme braking conditions, porous chromium is further fragmented to provide a chromium-rich nano-reinforced phase for the friction film, while rare earth oxides play a high-temperature lubrication role.
[0022] The advantages of the present invention include: (1) the main raw materials are low-cost powders such as iron powder, copper powder and graphite powder, and the rare earth element content is low, so the cost of the raw materials of the entire brake pad is not high; (2) the dispersion problem caused by nano powder is avoided, and the addition of rare earth elements also promotes the sintering densification process, which makes the preparation process of the entire brake pad material relatively simple, low in preparation cost and easy to mass produce; (3) the coordinated design of multiple components enables the brake pad material to have the ability to adaptively adjust as the braking conditions change. The high strength and wide temperature range lubrication ability also enable the brake pad to have a good match with the carbon ceramic brake disc at 400km / h and above. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a flowchart of a method for preparing a rare earth lubricated high-speed train brake pad.
[0024] Figure 2 Schematic diagram of the instantaneous friction coefficient curve of the brake pad prepared by Example 1 of the method of the present invention;
[0025] Figure 3 Schematic diagram of the instantaneous friction coefficient curve of the brake pad prepared by Example 2 of the method of the present invention;
[0026] Figure 4 Schematic diagram of the instantaneous friction coefficient curve of the brake pad prepared by Example 3 of the method of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below in conjunction with specific drawings and embodiments.
[0028] The present invention discloses a rare earth lubricated high-speed train brake pad and a preparation method thereof. The weight proportions of the components of the high-speed train brake pad are as follows:
[0029] Mixed powder of iron and copper: 50-80 parts by weight; mixed powder of flake graphite and granular graphite, 5-20 parts by weight; molybdenum disulfide powder: 0.5-5 parts by weight; alumina fiber: 0.5-5 parts by weight; high carbon ferrochrome powder: 1-10 parts by weight; chromium powder: 1-10 parts by weight; rare earth elements: 0.1-1.5 parts by weight.
[0030] Furthermore, the rare earth element is lanthanum or cerium; it is added in the form of a master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 15%-30%;
[0031] The average diameter of the alumina fiber is 0.1-10 μm, and the aspect ratio is 50-100.
[0032] Furthermore, in the mixed powder of flake graphite and granular graphite, the particle size of flake graphite is 250-600 μm, the particle size of granular graphite is 150-250 μm; and the ratio of flake graphite to granular graphite is 1:2-2:1;
[0033] The iron powder in the mixed powder of iron and copper is atomized iron powder, copper-coated iron powder or a mixture of the two in any proportion, and has a particle size of 38-80 μm; the copper powder is electrolytic copper powder, and has a particle size of 38-80 μm;
[0034] The ratio of iron to copper is 1:1-5:1.
[0035] Furthermore, the intermediate alloy is iron-lanthanum, iron-cerium, copper-lanthanum or copper-cerium.
[0036] like Figure 1 As shown, the present invention provides a method for preparing the above-mentioned high-speed train brake pad, and the method specifically comprises the following steps:
[0037] S1) Weigh each component according to the designed ratio, then weigh kerosene accounting for 1% of the weight of the powder, and transfer them into a double-conical mixing barrel for mixing;
[0038] S2) cold pressing the uniformly mixed powder obtained in S1) to obtain a cold blank;
[0039] S3) sintering the cold blank obtained in S2) at a certain temperature and pressure, cooling to below 100° C. after sintering, and taking it out to obtain a high-speed train brake pad.
[0040] Furthermore, the rotation speed of the mixing drum in S1) is 50-100 rpm, and the mixing time is 4-6h.
[0041] Furthermore, the cold pressing pressure in S2) is 300-600 MPa, and the holding time is 60-90 s.
[0042] Furthermore, the sintering process in S3) includes continuous low-temperature and high-temperature sintering; wherein the temperature of the continuous low-temperature sintering is 700-800°C, and the insulation time is 30-60min; the high-temperature sintering temperature is 1000-1200°C, and the insulation time is 30-90min, and the atmosphere is a hydrogen-nitrogen mixed gas; the pressure is 2-5MPa.
[0043] Furthermore, the method obtains a high-speed train brake pad having a density of not less than 87.2%, a hardness of not less than 47.5HRC, a compressive strength of not less than 246.5MPa, and a shear strength of not less than 39.3MPa.
[0044] Furthermore, the method obtains that the friction coefficient of the high-speed train brake pad is not less than 0.3, the braking distance is not greater than 7924m, and the total wear is not greater than 0.123cm in an emergency braking test at an initial speed of 400km / h. 3 / MJ.
[0045] Embodiment 1:
[0046] A rare earth-reinforced and lubricated high-speed train brake pad comprises the following components:
[0047] Mixed powder of iron and copper: 65 parts by weight; mixed powder of flake graphite and granular graphite, 14 parts by weight; molybdenum disulfide powder: 3 parts by weight; alumina fiber: 2 parts by weight; high carbon ferrochrome powder: 8 parts by weight; chromium powder: 7 parts by weight; rare earth elements: 1 part by weight.
[0048] The rare earth element is lanthanum, which is added in the form of copper-lanthanum master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 20%.
[0049] The alumina fiber has an average diameter of 5 μm and an aspect ratio of 60.
[0050] The mixed powder of flake graphite and granular graphite has a particle size of 500 μm for the flake graphite and a particle size of 230 μm for the granular graphite, and a ratio of 1:1 between the flake graphite and the granular graphite.
[0051] The mixed powder of iron and copper includes single atomized iron powder with a particle size of 75 μm and electrolytic copper powder with a particle size of 45 μm. After including the amount of the master alloy, the ratio of iron to copper is 1.5:1.
[0052] A method for preparing a rare earth-reinforced and lubricated high-speed train brake pad comprises the following steps:
[0053] S1) After weighing the above-designed components according to weight, weigh kerosene accounting for 1% of the weight fraction of the powder, transfer them into a double-conical mixing barrel for mixing at a speed of 70 rpm for 5 hours;
[0054] S2) cold pressing the uniformly mixed powder at a pressure of 400 MPa and a holding time of 70 s;
[0055] S3) Sintering the cold blank in a hot pressing sintering furnace under a hydrogen-nitrogen mixed atmosphere, with a low-temperature sintering temperature of 700°C and a heat preservation time of 50 min, a high-temperature sintering temperature of 1050°C and a heat preservation time of 70 min, a sintering pressure of 3 MPa during the whole process, cooling to below 100°C and taking out, keeping the pressure unchanged during the cooling process, and the instantaneous friction coefficient of the prepared train brake pad is as follows: Figure 2 shown.
[0056] Embodiment 2:
[0057] A rare earth-reinforced and lubricated high-speed train brake pad comprises the following components:
[0058] Mixed powder of iron and copper: 70 parts by weight; mixed powder of flake graphite and granular graphite, 12 parts by weight; molybdenum disulfide powder: 2 parts by weight; alumina fiber: 2 parts by weight; high carbon ferrochrome powder: 8 parts by weight; chromium powder: 5.2 parts by weight; rare earth elements: 0.8 parts by weight.
[0059] The rare earth element is cerium, which is added in the form of copper-cerium master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 20%.
[0060] The average diameter of the alumina fiber is 4 μm, and the aspect ratio is 70.
[0061] The mixed powder of flake graphite and granular graphite has a particle size of 600 μm for the flake graphite and a particle size of 180 μm for the granular graphite, and a ratio of 1:1.5 for the flake graphite and the granular graphite.
[0062] The mixed powder of iron and copper includes single copper-coated iron powder with a particle size of 75 μm and electrolytic copper powder with a particle size of 58 μm. After including the amount of the master alloy, the ratio of iron to copper is 2.5:1.
[0063] A method for preparing a rare earth-reinforced and lubricated high-speed train brake pad comprises the following steps:
[0064] S1) After weighing the above-designed components according to weight, weigh kerosene accounting for 1% of the weight fraction of the powder, transfer them into a double-conical mixing barrel for mixing at a speed of 80 rpm for 5.5 h;
[0065] S2) cold pressing the uniformly mixed powder at a pressure of 500 MPa for a holding time of 80 s;
[0066] S3) The cold blank is sintered in a hot pressing sintering furnace under a hydrogen-nitrogen mixed atmosphere, the low-temperature sintering temperature is 750°C, the heat preservation time is 55min, the high-temperature sintering temperature is 1100°C, the heat preservation time is 80min, the sintering pressure during the whole process is 4MPa, and the blank is cooled to below 100°C and taken out. The pressure is kept constant during the cooling process. The instantaneous friction coefficient of the prepared train brake pad is as follows: Figure 3 shown.
[0067] Embodiment 3:
[0068] A rare earth-reinforced and lubricated high-speed train brake pad comprises the following components:
[0069] Mixed powder of iron and copper: 60 parts by weight; mixed powder of flake graphite and granular graphite, 17 parts by weight; molybdenum disulfide powder: 2 parts by weight; alumina fiber: 3 parts by weight; high carbon ferrochrome powder: 10 parts by weight; chromium powder: 6.5 parts by weight; rare earth elements: 1.5 parts by weight.
[0070] The rare earth element is cerium, which is added in the form of iron-cerium master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 20%.
[0071] The average diameter of the alumina fiber is 3 μm, and the aspect ratio is 80.
[0072] The mixed powder of flake graphite and granular graphite has a particle size of 300 μm for the flake graphite and a particle size of 150 μm for the granular graphite, and a ratio of 2:1 between the flake graphite and the granular graphite.
[0073] The mixed powder of iron and copper is a mixture of atomized iron powder and copper-coated iron powder, the weight ratio of atomized iron powder is 50%, and the particle size is 62 μm; the copper powder is electrolytic copper powder, and the particle size is 38 μm.
[0074] The mixed powder of iron and copper, after including the amount of the master alloy, has a ratio of iron to copper of 4:1.
[0075] A method for preparing a rare earth-reinforced and lubricated high-speed train brake pad comprises the following steps:
[0076] S1) After weighing the above-designed components according to weight, weigh kerosene accounting for 1% of the weight fraction of the powder, transfer them into a double-conical mixing barrel for mixing, the speed of the mixing barrel is 90 rpm, and the mixing time is 6 hours;
[0077] S2) cold pressing the uniformly mixed powder at a pressure of 550 MPa for a holding time of 90 s;
[0078] S3) The cold blank is sintered in a hot pressing sintering furnace, the low temperature sintering temperature is 780℃, the temperature is kept for 40min, the high temperature sintering temperature is 1100℃, the temperature is kept for 65min, and the atmosphere is a hydrogen and nitrogen mixed gas. During the whole sintering process, the pressure is 2.5MPa, and it is cooled to below 100℃ and taken out. The pressure is kept constant during the cooling process. The instantaneous friction coefficient of the prepared train brake pad is as follows: Figure 4 shown.
[0079] The physical properties of the materials prepared in the above examples are shown in Table 1:
[0080] Table 1 Some physical performance parameters of the brake pads of the above embodiments 1-3 and comparative example 1
[0081]
[0082] An emergency braking test with an initial speed of 400 km / h was conducted on a 1:1 braking bench. The friction coefficient and wear amount are shown in Table 2:
[0083] Table 2 Average friction coefficient, braking distance and wear amount after braking of the brake pads of the above embodiments 1-3 and comparative example 1
[0084]
[0085] From Table 2 and Figure 1 It can be seen that in the case of continuous high-speed emergency braking, the friction coefficient of the materials of Examples 1-3 can be maintained above 0.3, with a relatively high and stable friction coefficient and low wear, which shows the rationality and practicality of the invention using rare earth elements.
[0086] The above is a detailed introduction to a rare earth lubricated high-speed train brake pad and a preparation method provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present application.
[0087] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0088] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0089] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0090] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A rare earth lubricated high-speed train brake pad and a preparation method, characterized in that: The weight proportions of the various components of the high-speed train brake pad are: Mixed powder of iron and copper: 50-80 parts by weight; mixed powder of flake graphite and granular graphite: 5-20 parts by weight; molybdenum disulfide powder: 0.5-5 parts by weight; alumina fiber: 0.5-5 parts by weight; high carbon ferrochrome powder: 1-10 parts by weight; Chromium powder: 1-10 parts by weight; rare earth element: 0.1-1.5 parts by weight.
2. The high-speed train brake pad according to claim 1, characterized in that: The rare earth element is lanthanum or cerium, which is added in the form of master alloy powder, wherein the weight fraction of the rare earth element in the master alloy powder is 15%-30%; The average diameter of the alumina fiber is 0.1-10 μm, and the aspect ratio is 50-100.
3. The high-speed train brake pad according to claim 1, characterized in that: The mixed powder of flake graphite and granular graphite has a particle size of 250-600 μm for the flake graphite and a particle size of 150-250 μm for the granular graphite; and the ratio of flake graphite to granular graphite is 1:2-2:1; The iron powder in the mixed powder of iron and copper is atomized iron powder, copper-coated iron powder or a mixture of the two in any proportion, and has a particle size of 38-80 μm; the copper powder is electrolytic copper powder, and has a particle size of 38-80 μm; The ratio of iron to copper is 1:1-5:
1.
4. The high-speed train brake pad according to claim 2, characterized in that: The intermediate alloy is iron-lanthanum, iron-cerium, copper-lanthanum or copper-cerium.
5. A method for preparing a high-speed train brake pad according to any one of claims 1 to 4, characterized in that: The method specifically comprises the following steps: S1) Weighing each component according to the designed ratio, and then weighing kerosene accounting for 1% of the weight fraction of the powder, and transferring them into a double-conical mixing barrel for mixing to obtain a mixed powder; S2) cold pressing the mixed powder obtained in S1) to obtain a cold blank; S3) sintering the cold blank obtained in S2) at a certain temperature and pressure, cooling to below 100° C. after sintering, and taking it out to obtain a high-speed train brake pad.
6. The method according to claim 5, characterized in that The rotation speed of the mixing drum in S1) is 50-100 rpm, and the mixing time is 4-6h.
7. The method according to claim 5, characterized in that The cold pressing pressure in S2) is 300-600 MPa, and the holding time is 60-90 s.
8. The method according to claim 5, characterized in that The sintering process in S3) includes continuous low-temperature and high-temperature sintering; wherein the temperature of the continuous low-temperature sintering is 700-800°C, and the insulation time is 30-60min; the temperature of the high-temperature sintering is 1000-1200°C, and the insulation time is 30-90min, the atmosphere is a hydrogen-nitrogen mixed gas, and the pressure is 2-5MPa.
9. The method according to claim 5, characterized in that The high-speed train brake pad obtained by the method has a density of not less than 87.2%, a hardness of not less than 47.5HRC, a compressive strength of not less than 246.5MPa, and a shear strength of not less than 39.3MPa.
10. The method according to claim 5, characterized in that The method obtains that the friction coefficient of the high-speed train brake pad is not less than 0.3, the braking distance is not greater than 7924m, and the total wear amount is not greater than 0.123cm in an emergency braking test at an initial speed of 400km / h. 3 / MJ.
Citation Information
Patent Citations
A Ferrous Powder Metallurgy Friction Material and Its Preparation Method
CN104399970B
A kind of iron-based composite friction material for clutch and its preparation method
CN106086718B
A powder metallurgical brake pad compatible with a carbon ceramic brake disc and its preparation method
CN112059171B
Copper-base powder metallurgy friction material for high-speed linear brake and preparing method of copper-base powder metallurgy material
CN107245676A
Fiber reinforced copper-based brake pad for high-speed train and preparation method as well as detection method of friction braking performance of fiber reinforced copper-based brake pad
CN109469697A